2013
DOI: 10.1111/dme.12232
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonylureas and risk of cardiovascular disease: systematic review and meta‐analysis

Abstract: Results suggest that sulphonylurea use may elevate the risk of cardiovascular disease among patients with diabetes. This meta-analysis expands the pool of studies evaluating cardiovascular mortality compared with prior observations while using adjusted estimates, and assessing an additional outcome of a composite cardiovascular event. This finding warrants consideration in clinical practice when other treatment options may be available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 49 publications
8
82
0
9
Order By: Relevance
“…Despite the similarities between these sulfonylureas, they have different extra pancreatic effects and may have different effects on cardiovascular disease. However, their effects on cardiovascular disease remain unclear [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the similarities between these sulfonylureas, they have different extra pancreatic effects and may have different effects on cardiovascular disease. However, their effects on cardiovascular disease remain unclear [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains unclear whether the administration of sulfonylureas impedes cardiovascular disease onset, which is the endpoint [32], the outcomes of the present study, i.e., blood PAI-1 levels, could serve as a surrogate marker for cardiovascular disease onset [3]. In the present study, glib-doi: 10.7243/2050-0866-7-1 enclamide, gliclazide, and glimepiride were compared with the placebo, and no significant decrease in blood PAI-1 levels was observed after using the agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of the newer shorter-acting antidiabetic sulfonylureas, such as gliclazide and glimepiride, do not appear to interfere with cardioprotection (Wu et al, 2007). A recent metaanalysis has confirmed that sulphonylurea use may elevate the risk of cardiovascular disease among patients with diabetes (Phung et al, 2013), although one long-term clinical outcome study failed to report any increase in cardiovascular events in diabetic patients treated with glibenclamide compared with gliclazide (Juurlink et al, 2012).…”
Section: Antidiabetic Therapymentioning
confidence: 99%
“…Indeed, several recent studies suggested that patients treated with sulfonylureas have increased cardiovascular morbidity compared with patients treated with metformin [45][46][47] . Therefore, it would be of interest to compare the effects of prior treatment of DPP-4 inhibitors with prior treatment with metformin in experimental models of stroke or in patients who suffer a stroke.…”
Section: Ref Design N Agent Resultsmentioning
confidence: 99%